2020
DOI: 10.1007/s10640-020-00486-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Air Pollution on COVID-19 Related Mortality in Northern Italy

Abstract: Long-term exposure to ambient air pollutant concentrations is known to cause chronic lung inflammation, a condition that may promote increased severity of COVID-19 syndrome caused by the novel coronavirus (SARS-CoV-2). In this paper, we empirically investigate the ecologic association between long-term concentrations of area-level fine particulate matter (PM 2.5) and excess deaths in the first quarter of 2020 in municipalities of Northern Italy. The study accounts for potentially spatial confounding factors re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
102
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(109 citation statements)
references
References 41 publications
4
102
2
1
Order By: Relevance
“…The second group’s variables concerned air pollutants, regarding PM 10 and PM 2.5 . Indeed, considering the complexity due to the big amount of air pollutants, in this analysis we chose to focus on those with harmful effects on human health in terms of chronic health effects (that are consistent with [ 39 , 40 ]). So, in this analysis the average annual values of daily concentration (µg/m 3 ) of PM 2.5 and PM 10 particles were considered as independent variables.…”
Section: The Case Study and The Methodology Proposedmentioning
confidence: 99%
See 1 more Smart Citation
“…The second group’s variables concerned air pollutants, regarding PM 10 and PM 2.5 . Indeed, considering the complexity due to the big amount of air pollutants, in this analysis we chose to focus on those with harmful effects on human health in terms of chronic health effects (that are consistent with [ 39 , 40 ]). So, in this analysis the average annual values of daily concentration (µg/m 3 ) of PM 2.5 and PM 10 particles were considered as independent variables.…”
Section: The Case Study and The Methodology Proposedmentioning
confidence: 99%
“…In addition, as suggested by Coker et al [ 39 ], several control variables have been introduced that may plausibly have effects on the hospitalization rate for each province, including population density/average age of population/ratio between the number of residents older than 40, 50 and 60 years old and the amount of residents/percentage of women/percentage of men/ratio between the public green space and the residents on each province/ratio between workers and residents.…”
Section: The Case Study and The Methodology Proposedmentioning
confidence: 99%
“…Another study in Italy reported a positive association between ambient PM 2.5 concentration and excess COVID-19 related mortality (38). A one-unit increase in PM 2.5 concentration (µg/m3) was associated with a 9% increase in the COVID-19 related fatality (38). In Peru, the higher rates of spread of COVID-19 in Lima were associated with the previous longterm PM 2.5 exposure (41).…”
Section: Long-term Exposure To Air Pollution and Covid-19mentioning
confidence: 98%
“…Warm-season may not have a role in spreading viral infection (35). Another study in Italy reported a positive association between ambient PM 2.5 concentration and excess COVID-19 related mortality (38). A one-unit increase in PM 2.5 concentration (µg/m3) was associated with a 9% increase in the COVID-19 related fatality (38).…”
Section: Long-term Exposure To Air Pollution and Covid-19mentioning
confidence: 99%
“…Air pollution is a global health concern and numerous studies have found links between air pollution and both respiratory and chronic diseases [1,2,3,4]. Since the start of the COVID-19 pandemic, several studies have found links between air pollution and COVID-19 incidence and mortality [5,6,7,8,9]. The present study aims at determining whether there is a link between air pollution and COVID-19 deaths at the municipality level in Sweden.…”
Section: Introductionmentioning
confidence: 93%